Effect of intercropping peonies under walnut trees for growth and development of roots in two kinds of soil. (October 2019) - Xu, R; Wang, Z J; Luo, Y; Zhang, N; Liang, C; Zhu, G P
Abstract: To increase the economic benefit and to reduce the cost at early stages of walnut (Juglans regia L.) cultivation, the interaction of roots between walnut cultivar Zhongsong No. 1 and peony (Paeonia ostii T. Hong & J. X. Zhang) was studied. The growth rhythm per year and the vertical and horizontal distribution of roots were measured. Statistically evaluated data for five consecutive years of study using a random sampling method at yellow-brown and red soil types were presented. The results showed that walnut had three root growth peaks per year, whereas peony had two peaks. At vertical distribution of roots, walnut was concentrated under 40 cm and peony under 20 cm of soil. At vertical distribution of roots, walnut was concentrated 40 -120 cm far from the tree, but peony was 20 -60 cm. We are confident that the root growth and development when intercropping of peony was carried out under walnut trees was alternating and the negative influence was low. So, the cultivation model of "intercropping peony under walnut trees" was suitable at the Luoyang area, Henan province, but the cultivation distance ought to be at 120 -180 cm.